2006
DOI: 10.1136/gut.2005.064543
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin A inhibits pancreatic stellate cell activation: implications for treatment of pancreatic fibrosis

Abstract: Background and aims: Activated pancreatic stellate cells (PSCs) are implicated in the production of alcohol induced pancreatic fibrosis. PSC activation is invariably associated with loss of cytoplasmic vitamin A (retinol) stores. Furthermore, retinol and ethanol are known to be metabolised by similar pathways. Our group and others have demonstrated that ethanol induced PSC activation is mediated by the mitogen activated protein kinase (MAPK) pathway but the specific role of retinol and its metabolites all-tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
80
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(86 citation statements)
references
References 40 publications
6
80
0
Order By: Relevance
“…Also uncertain is the contribution of impaired glucose tolerance to diminished pancreatic β-cell function and mass associated with type 2 diabetes (5). GSIS relies on the pancreas, and pancreas development, islet formation, and function require normal vitamin A nutriture (6)(7)(8). Vitamin A restriction during development impairs islet development and promotes glucose intolerance in adult rodents.…”
mentioning
confidence: 99%
“…Also uncertain is the contribution of impaired glucose tolerance to diminished pancreatic β-cell function and mass associated with type 2 diabetes (5). GSIS relies on the pancreas, and pancreas development, islet formation, and function require normal vitamin A nutriture (6)(7)(8). Vitamin A restriction during development impairs islet development and promotes glucose intolerance in adult rodents.…”
mentioning
confidence: 99%
“…It is currently known that antioxidants can be used as a treatment strategy in various pathologies, including ethanol consumption. It has been found that activation of pancreatic stellate cells is inhibited when these are incubated with antioxidants (Apte et al, 2000;McCarroll et al, 2006). This is why vitamin A, an antioxidant, may represent a potential treatment strategy for the damage produced by ethanol.…”
Section: Introductionmentioning
confidence: 99%
“…This vitamin A-storage might not only be a mere feature of quiescent PSC, but functionally contribute to the maintenance of this state. McCarroll et al [20] showed that retinol and its metabolites (all-trans retinoic acid and 9-retinoic acid) inhibited the induction of a-SMA expression in PSCs. Retinol and its metabolites induced quiescence in culture-activated PSCs, in association with a significant decrease in the activation of mitogen-activated protein (MAP) kinases [20].…”
Section: Activation Of Pscsmentioning
confidence: 99%
“…McCarroll et al [20] showed that retinol and its metabolites (all-trans retinoic acid and 9-retinoic acid) inhibited the induction of a-SMA expression in PSCs. Retinol and its metabolites induced quiescence in culture-activated PSCs, in association with a significant decrease in the activation of mitogen-activated protein (MAP) kinases [20]. It is, therefore, tempting to speculate that retinoic acids are involved in the maintenance of a quiescent phenotype, through the binding to their nuclear receptors and the regulation of gene expression.…”
Section: Activation Of Pscsmentioning
confidence: 99%